2010
DOI: 10.2202/1548-923x.1893
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of a Peer Learning Approach to Pediatric Clinical Education

Abstract: With changing trends in the acute pediatric setting, there is concern that nursing students are not provided with sufficient opportunities to develop required clinical competencies. Peer learning can assist students in achieving learning objectives through efficient and effective use of limited resources. In this study the perceptions of students and clinical instructors in their use of peer learning are described. A qualitative descriptive design with semi-structured interviews was used. A convenience sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 0 publications
6
42
0
Order By: Relevance
“…As such CIs are advised to evaluate whether the required learning competencies are achieved particularly in groups of students with varying clinical strengths and learning needs. [51] Findings from this study were similar to a study by Brown, Herd, Gwynneth, and Moya [52] that strongly emphasized the need for support during the first year and, in particular, during the first placement. Houghton et al [50] concur that novice students, particularly those in initial days and years of clinical placements need more direct supervision and support while senior students can work independently and only need some environmental supervision.…”
Section: Discussionsupporting
confidence: 83%
“…As such CIs are advised to evaluate whether the required learning competencies are achieved particularly in groups of students with varying clinical strengths and learning needs. [51] Findings from this study were similar to a study by Brown, Herd, Gwynneth, and Moya [52] that strongly emphasized the need for support during the first year and, in particular, during the first placement. Houghton et al [50] concur that novice students, particularly those in initial days and years of clinical placements need more direct supervision and support while senior students can work independently and only need some environmental supervision.…”
Section: Discussionsupporting
confidence: 83%
“…Junior learners felt more comfortable and less intimidated when paired with senior learners or residents compared with being paired 1 : 1 with experienced professionals . Other cited benefits of the tiered ratio were diverse learning experiences and shared knowledge between learners at different levels …”
Section: Resultsmentioning
confidence: 99%
“…Studies of nursing students have reported increased opportunity for discussion and reflection, improved problem‐solving ability (Hellström‐Hyson, Mårtensson, & Kristofferzon, ; Holst & Hörberg, ; Stenberg & Carlson, ) and self‐efficacy (Hellström‐Hyson et al., ; Pålsson, Mårtensson, Swenne, Ädel, & Engström, ; Ruth‐Sahd, ). Furthermore, having a peer to work with has been shown to promote feelings of safety and of not being alone, which decreased anxiety (Chojecki et al., ; Stenberg & Carlson, ). Students reported receiving support by working in pairs; they could test their knowledge and return to the security of the pair to enrich their knowledge and then try their wings once again (Holst & Hörberg, ).…”
Section: Introductionmentioning
confidence: 99%